Program Pemberdayaan Usaha Mikro di Kelurahan Pasar Ambacang Kota Padang - Nadya Vadyla; Hasbullah Malau (PUBLICNESS: Journal of Public Administration studies, 2022)
The purpose of this study is to analyze the factors constraining the Online Single Submission System (OSS) in the UMKM program in Pasar Ambacang Village, Padang City. The background of this study explains that UMKM is still not developing because there is no review carried out by the Office of the development of UMKM groups in Pasar Ambacang Village, Padang City. This research was conducted using a descriptive qualitative approach. Test the validity of the data with triangulation techniques. Collecting data through interviews, documentation. The data analysis technique that the researcher uses is the manual data analysis procedure (MDAP). The results of the study explain that there are several obstacles experienced by the community related to this OSS policy, namely the community's understanding of technology is still low and there is still a lack of socialization of the OSS system from the kelurahan so that it is necessary to increase socialization by the Pasar Ambacang Village.  thus this OSS system can be used by easy for the people.